Indicadores antecedentes da produção industrial brasileira : o cálculo das probabilidades de reversão (turning points) - Bossoes, Alex Gomes (2008)
Leading indicators are a method based on the examination of a cycle as an empirical phenomenon; the concept of business cycles appeared in middle of the 20th century by Wesley Mitchell and Arthur Burns. It is one technique that searchs to anticipate the behavior of one given serie (reference). Diverse methods exist for its construction. In this study it is considered a construction of an indicator for Produção Industrial Brasileira (Brazilian Industrial Production) with the objective of calculating the probabilities of the turning point. For this, the series have been filtered and standardized. The Granger criterion gave basis for the selection. A balance with cross correlograms of the chosen sequencies (series) occurs for the composition of the indicator and for the calculation of the probability of reversion the methodology of Neftçi (1982) was used. Around 290 sequencies (series) were analyzed and only 9 were selected for the construction of the indicator. Some samples periods of time have been studied from January of 1992 to December of 2006 for the calculation of the probabilities, these also have been calculated by another method (probit) to compare with the methodology of Neftçi. The results demonstrate the great utility of this tool for forecasting of the cyclical movements of economic series. It is a technique that can be used to help with public politics and private policy making.